2017
DOI: 10.1186/s11671-016-1772-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure of Poly(Acrylic Acid) Adsorption Layer on the Surface of Activated Carbon Obtained from Residue After Supercritical Extraction of Hops

Abstract: The nanostructure of poly(acrylic acid) (PAA) adsorption layer on the surface of mesoporous-activated carbon HPA obtained by physical activation of residue after supercritical extraction of hops was characterized. This characterization has been done based on the analysis of determination of adsorbed polymer amount, surface charge density, and zeta potential of solid particles (without and in the PAA presence). The SEM, thermogravimetric, FTIR, and MS techniques have allowed one to examine the solid surface mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…A higher doping level was obtained using a stronger polyacid, demonstrating lower pKa values. The pKa values of PSS, PAA, and TA are known to be ~1, ~4.5, and ~8.5, respectively; PSS is the strongest polyacid and TA is the weakest polyacid [ 21 , 22 , 23 ]. The proportional relationship between the doping level of PANI and the strength of the polyacids can be attributed to the fact that stronger polyacids have a greater amount of negatively charged functional groups, which can dope PANI more effectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher doping level was obtained using a stronger polyacid, demonstrating lower pKa values. The pKa values of PSS, PAA, and TA are known to be ~1, ~4.5, and ~8.5, respectively; PSS is the strongest polyacid and TA is the weakest polyacid [ 21 , 22 , 23 ]. The proportional relationship between the doping level of PANI and the strength of the polyacids can be attributed to the fact that stronger polyacids have a greater amount of negatively charged functional groups, which can dope PANI more effectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, polyacids of different acidity and molecular structure, i.e., PSS, PAA, and TA, are used as dopants to fabricate PANI-based LbL films. PSS is a strong polyacid (pKa: 1) [ 21 ] and PAA is a weak polyacid (pKa: 4.5) [ 22 ], while TA is relatively small and the weakest polyacid (pKa: ~8.5) [ 23 , 24 ]. It is found that the acidic strength of polyacids assembled with PANI affects the doping level of PANI in a consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…The most common used adsorbent for wastewater treatment system is bare activated carbon, owing to its large specific surface area [21]. However, the capability of carbon material to unspecifically adsorb all kinds of pollutant molecules (both dyes and organic species) has led to use it in the final step of the removal treatment [25].…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon (AC) is a material used for sewage treatment and gas filters; it is also used in the chemical, textile, petrochemical, and pharmaceutical industries among others. Carbon activation can take place by using physical or chemical activation.…”
Section: Introductionmentioning
confidence: 99%